School Well-Being dengan Motivasi Belajar Siswa Administrasi Perkantoran Kelas XI SMKN 3 Padang - Frihapma Semita Ade; Miftahul Ilmi Ikhwani; Ria Okfrima (Psyche 165 Journal, 2023)
The existence of a representative school will indirectly provide learning comfort for students, neat environmental management, clean classrooms, and a conducive atmosphere are one of the supporting factors for the success of the teaching and learning process. When students feel comfortable, motivation to learn will arise from within them. This study aims to determine the relationship between school well-being and learning motivation in class XI students of the Office Administration Program at SMKN 3 Padang. The research variables are School Well-Being (X), Learning Motivation (Y). The data collection method is distributing questionnaires with a sample of 95 students. The subject of this study used the Saturated Sample technique. Measuring tools used in this study are the School Well-Being scale, and the Learning Motivation Scale.The data analysis method used to test the hypothesis in this study is to use the Pearson product moment statistical test with the help of IBM SPSS 21.0, which shows that r = 0.575 with a significance level of p = 0.000 <0.01, meaning that the hypothesis is acceptable and there is there is a very significant relationship between school well-being and learning motivation in class XI students majoring in Office Administration at SMKN 3 Padang, meaning that if school well-being is high, the learning motivation for class XI students majoring in Office Administration at SMKN 3 Padang is high. Conversely, if school well-being is low, the learning motivation of class XI students majoring in Office Administration at SMKN 3 Padang is also low, meaning that the research hypothesis is accepted. The effective contribution of the School Well-Being variable with learning motivation is 33%.